Application of a Yeast Biosurfactant in the Removal of Heavy Metals and Hydrophobic Contaminant in a Soil Used as Slurry Barrier - R. D. Rufino; G. I. B. Rodrigues; G. M. Campos-Takaki; L. A. Sarubbo; S. R. M. Ferreira (Applied and Environmental Soil Science)
This work describes the application of a yeast biosurfactant in the removal of heavy metals and petroleum derivate in a soil used as slurry barrier using a triaxial permeability apparatus. Test specimens were prepared with soil and contaminants for percolation of the biosurfactant. The hydraulic conductivity measured along percolation of the fluids showed that the biosurfactant reduced significantly the soil permeability, demonstrating its applicability as an additive in reactive barriers. The crude biosurfactant removed around 96% Zn and Cu and reduced the concentrations of Pb, Cd, and Fe from the test specimen. The biosurfactant removed 20% of the waste oil using the permeability apparatus. The results show that the biosurfactant can be applied in new technologies where the removal of heavy metals and petroleum derivates is desirable. These results demonstrate the versatility of biomolecules with amphipathic nature, a property that makes them increasingly competitive with real possibilities for use in industries.